Decrease in Efficacy of Warfarin as a Result of Drug-Drug Interaction (Case Report) - N. T. Vatutin; G. G. Taradin; G. A. Ignatenko; E. S. Gasendich; A. V. Harchenko; I. B. Povaljaeva (Рациональная фармакотерапия в кардиологии)
The one of the main aims in modern clinical pharmacology is to provide safe and effective therapy considering a frequent administration of several drugs having different drug-drug interactions. Warfarin belongs to the number of popular anticoagulants which along with its efficiency not infrequently alters anticoagulant characteristics when administered with other drugs and food products. A case of a decrease in the efficacy of warfarin in a patient with mitral stenosis while taking a combined choleretic drug is presented in the article. The components of this choleretic drug (dry animal bile, dry garlic extract, dry nettle extract, activated charcoal) could impair the absorption of warfarin, increase intestinal absorption of vitamin K, and have a negative effect on the anticoagulant effect of warfarin. Management of patients receiving anticoagulants should be performed in accordance with clinical recommendations. Prescription of drugs, including multicomponent ones, without proven efficacy, for such patients should be considering the potential drug interaction.